ANALISIS PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUTUSAN MAHASISWA MEMILIH TEMPAT INDEKOS DENGAN HARGA SEWA INDEKOS SEBAGAI VARIABEL MODERASI - Kurniawan, Andre (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyze the significance of the influence of location, facilities and rental rates boarder partially on student decision choosing a boarder at the Village Panularan Laweyan District of the city of Surakarta. To analyze the effect of moderating the influence of homestay rental rates and facilities location to choose a student's decision boarder at the Village Panularan Laweyan District of the city of Surakarta. In conclusion, no significant influence on the decision of the location of the students choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. There was a significant effect of the facility to choose a student's decision boarder at the Village Panularan Laweyan District of the city of Surakarta. There was a significant influence on the decision of the rental price boarder students choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Lodger rental prices do not moderate influence on the decision of the location of the student choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Lodger rental prices do not moderate the effect of the facility to the decision of the student choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Keywords: location, facilities, rental prices lodger, students choose a lodger decision